1999
DOI: 10.1212/wnl.53.6.1205
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and therapeutic observations in aromatic l -amino acid decarboxylase deficiency

Abstract: The movement disorder in AADC deficiency, particularly the characteristic eye movement abnormalities, should facilitate the identification of patients with this rare but possibly underrecognized disorder. Directed therapy of the underlying dopamine and norepinephrine deficiency may be beneficial in some cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 27 publications
3
59
0
Order By: Relevance
“…In some patients, convulsion due to hypoglycemia was reported. (Korenke et al, 1997;Swoboda et al, 1999Swoboda et al, , 2003 Sleep disorder was also observed in a part of patients, for amount of melatonin is decreased in patients with AADC deficiency. Melatonin is synthesized from serotonin and amount of serotonin often decrease in patients with AADC deficiency.…”
Section: Wwwintechopencommentioning
confidence: 98%
See 1 more Smart Citation
“…In some patients, convulsion due to hypoglycemia was reported. (Korenke et al, 1997;Swoboda et al, 1999Swoboda et al, , 2003 Sleep disorder was also observed in a part of patients, for amount of melatonin is decreased in patients with AADC deficiency. Melatonin is synthesized from serotonin and amount of serotonin often decrease in patients with AADC deficiency.…”
Section: Wwwintechopencommentioning
confidence: 98%
“…(See Fig.3) Patients of AADC deficiency showed intermittent oculogyric crisis and dystonia of four limbs before 6 month-old. (Korenke et al, 1997;Swoboda et al, 1999Swoboda et al, , 2003 Irritability, ocular convergence spasm, facial dystonia, myoclonus, and dysfunction of voluntary movements were often observed. Hypotonia and increase of deep tendon reflex were observed.…”
Section: Aromatic Amino Acid Decarboxylase (Aadc) Deficiencymentioning
confidence: 99%
“…Because of the reduced synthesis of monoamines, patients with AADC deficiency usually have profound developmental delay, microcephaly, and hypotonia since 2 to 6 months of age [1,[14][15][16][17]. They also frequently have irritability and feeding difficulties, tremor, episodic dystonia, oculogyric crisis and parkinsonian symptoms.…”
Section: Aromatic Amino Acid Decarboxylase Deficiencymentioning
confidence: 99%
“…High-dose Vitamin B6 and folinic acid are also frequently used. However, the treatment effect is highly variDisorders of monoamine metabolisms Wang-Tso Lee able, and frequently unsatisfactory [12,17]. Anti-epileptic drugs had been tried in some patients with AADC deficiency without definite benefits [1].…”
Section: Aromatic Amino Acid Decarboxylase Deficiencymentioning
confidence: 99%
“…Hyland and Clayton (Hyland and Clayton, 1990;Hyland et al, 1992). To date, more than 80 cases have been reported worldwide (Korenke et al, 1997;Maller et al, 1997;Abeling et al, 1998;Swoboda et al, 1999Swoboda et al, , 2003Brautigam et al, 2000;Fiumara et al, 2002;Pons et al, 2004;Tay et al, 2007;Brun et al, 2010;Montioli et al, 2013). Patients with AADC deficiency present with hypotonia, oculogyric crises, hypokinesia, and developmental delay, and 96% of these deficiencies become clinically evident during infancy or childhood (Manegold et al, 2009;Brun et al, 2010;Hwu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%